Curriculum and Arabic Reading Material Design for Islamic Education in Multicultural Settings: A Case of a State Islamic University: تصميم المنهج ومواد القراءة العربية لتخصص التربية الإسلامية في سياقات متعددة الثقافات: دراسة حالة في جامعة إسلامية حكومية - Anam, Syamsul; Maulana, Asep (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Despite the growing recognition of multicultural values in education, Arabic reading materials that explicitly incorporate multicultural themes remain limited, especially within Islamic higher education. This study aims to fill this gap by: (1) designing a multicultural-based reading syllabus, (2) developing appropriate reading materials, (3) assessing the feasibility of both, and (4) evaluating their effectiveness in improving students’ reading skills. Employing a mixed-methods approach with field research, the development follows Borg and Gall’s ten-step model. Data were collected through observation, interviews, documentation, questionnaires, and reading tests, involving second-semester students from classes A7 and A8 of the Islamic Education Program at FTIK, IAIN Jember. Results show that the syllabus aligns with subject-centered design and KKNI standards, while the developed materials reflect multicultural values such as tolerance, justice, equality, and humanity. Statistical analysis confirms a significant improvement in students’ reading abilities after using the materials. The study concludes that integrating multicultural themes into Arabic reading instruction not only enhances language proficiency but also cultivates inclusive and culturally responsive learning. These findings suggest the potential for broader implementation of multicultural approaches in Arabic language curricula across Islamic higher education institutions.